2020
DOI: 10.5194/nhess-20-2365-2020
|View full text |Cite
|
Sign up to set email alerts
|

Fire Weather Index: the skill provided by the European Centre for Medium-Range Weather Forecasts ensemble prediction system

Abstract: Abstract. In the framework of the EU Copernicus programme, the European Centre for Medium-Range Weather Forecasts (ECMWF) on behalf of the Joint Research Centre (JRC) is forecasting daily fire weather indices using its medium-range ensemble prediction system. The use of weather forecasts in place of local observations can extend early warnings by up to 1–2 weeks, allowing for greater proactive coordination of resource-sharing and mobilization within and across countries. Using 1 year of pre-operational service… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 48 publications
(57 reference statements)
2
28
0
Order By: Relevance
“…By systematically evaluating the ECMWF ensemble forecast system performance to reproduce fire weather index (FWI) from observing stations at the global scale, the authors demonstrate the capacity of this ensemble approach to be reasonably accurate up to 10 days ahead, especially for some of the largest fires that took place in 2017, namely in Chile and Portugal. Their results confirm that early warning could be extended by up to 1-2 weeks by using advanced numerical weather models, allowing for better coordination of resourcesharing and mobilization within and across countries (Di Giuseppe et al, 2020).…”
Section: The Prediction Of Fire-weather Indicessupporting
confidence: 56%
See 1 more Smart Citation
“…By systematically evaluating the ECMWF ensemble forecast system performance to reproduce fire weather index (FWI) from observing stations at the global scale, the authors demonstrate the capacity of this ensemble approach to be reasonably accurate up to 10 days ahead, especially for some of the largest fires that took place in 2017, namely in Chile and Portugal. Their results confirm that early warning could be extended by up to 1-2 weeks by using advanced numerical weather models, allowing for better coordination of resourcesharing and mobilization within and across countries (Di Giuseppe et al, 2020).…”
Section: The Prediction Of Fire-weather Indicessupporting
confidence: 56%
“…heatwaves, floods or tropical cyclones) reached a fairly mature standard, however, the forecast of wildfire prone conditions still lags behind with fire danger indicators mostly relying on environmental monitoring. In 2020, a study led by Francesca Di Giuseppe (Di Giuseppe et al, 2020) published in NHESS suggested extending fire danger warnings with the use of the most advanced weather forecast model available, i.e.…”
Section: The Prediction Of Fire-weather Indicesmentioning
confidence: 99%
“…Crucially, studies on future fire risk projections indicate that fire impacts in Southern Europe should experience a turning point in the near future, shifting from currently decreasing trends to a high impact trajectory 8 , 9 . Overall, due to the large impacts of fire on ecosystem services and multiple social and economic assets, there is an urgent need for more detailed quantitative studies analyzing the changing relationships between fire weather and realized impacts in continental Europe 10 , 11 .…”
mentioning
confidence: 99%
“…However, its simplicity of implementation has made it a popular choice in many countries, and it has been shown to perform reasonably well in global analyses and in ecosystems very dissimilar to the boreal forest 13 17 . The FWI system is also the rating system for fire monitoring adopted in many European countries and a principal component of the Copernicus Emergency Management Service CEMS 11 . All the components of the FWI system only rely on weather forcings, and neither information on the vegetation status nor on the ignition are taken into account.…”
mentioning
confidence: 99%
“…Traditional approaches for forecasting seasonal changes in fire weather relied on developing fire weather and danger indices that, often, seek to estimate fuel moisture and potential fire spread depending on past meteorological conditions. These indices have shown mixed success in predicting fire danger [29,30], and they have not been exempt from criticism [31]. Developing an early warning system for catastrophic fire, which predicts when and where critical wildfires will occur, as well as educating the populace on how to interpret these predictions, has become an increasing necessity [3].…”
mentioning
confidence: 99%